Host effects in high ectomycorrhizal diversity tropical rainforests on ultramafic soils in New Caledonia. (June 2019) - Carriconde, Fabian; Gardes, Monique; Bellanger, Jean-Michel; Letellier, Kelly; Gigante, Sarah; Gourmelon, Véronique; Ibanez, Thomas; McCoy, Stéphane; Goxe, Julie; Read, Jennifer; Maggia, Laurent
Abstract: Tropical rainforests have been thought to have low prevalence and diversity of ectomycorrhizal symbioses. However, to date, tropical regions have been poorly sampled for ectomycorrhizal fungi. Here, we investigated ectomycorrhizal fungal community diversity and the role of host plants in shaping this diversity in three main ultramafic rainforests in New Caledonia, an archipelago renowned for its exceptional plant diversity and recognized as a biodiversity hotspot. Sampling of ectomycorrhizal root tips and fruit bodies in Nothofagus aequilateralis -dominated, Arillastrum gummiferum -dominated and mixed rainforests showed high fungal diversity with, in total, 28 lineages and 311 operational taxonomic units (OTUs), of which 95% might be endemic. We also found that host preference and host density influenced ectomycorrhizal community composition and contributed to the high fungal diversity of New Caledonian rainforests. Finally, the /cortinarius lineage dominated the below- and above-ground communities, which suggests that this lineage plays a central role in ultramafic ecosystems functioning. Highlights: High and unique diversity of ectomycorrhizal fungi in New Caledonian rainforests. The/cortinarius lineage dominates New Caledonian ectomycorrhizal fungal communities. Host preference and host density may influence New Caledonian fungal communities.